EFEKTIVITAS PENERAPAN MODEL DISCOVERY LEARNING DALAM PEMBELAJARAN IPS SISWA KELAS VII SMP MUJAHIDIN PONTIANAK - Jayanti, Jayanti; Noor, Agus Sastrawan; Achmadi, Achmadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research is an experimental study which aims to determine the effectiveness of the application of discovery learning models in social studies learning for seventh grade students of Pontianak Mujahidin Middle School. The background in this study is that when learning takes place many students feel bored and sleepy in class so that the learning outcomes look less satisfying. This is seen from the value of the daily test of students of class VII who are still many who have not reached the KKM 75. The method used in this study is the experimental method, the research design used is One-Group Pretest-Posttest design. The data sources in this study were all seventh grade students of Pontianak Mujahidin Middle School and the values of the pretest, posttest students. From the results of the research and discussion, it can be concluded that the students' learning outcomes before applying the Discovery Learning learning model are low in average values of 51.45 and the percentage of completeness is only 7.14%. While the learning outcomes of students who apply the Discovery Learning learning model on average is 78.61 and the completeness percentage is 71.43%. The effectiveness of discovery learning is 1.95 and is high. So it can be seen that by applying discovery learning learning models can improve student learning outcomes and are very effective to apply. Keywords:    Discovery Learning, Learning Outcomes, Social Studies Subject